Answer:
C
Step-by-step explanation:
Answer:
okkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkk
Answer:
41, x=-5
Step-by-step explanation:
m<DEY = m<FEY, by angle bisector theorem
(9x-4) = 41
9x = 45
x = 5
m<DEY = 41
Answer:
b.
Step-by-step explanation:
The given function is
![\sec x=-\frac{2\sqrt{3} }{3},\:\:for\:\:\frac{\pi}{2}\le x \le \pi](https://tex.z-dn.net/?f=%5Csec%20x%3D-%5Cfrac%7B2%5Csqrt%7B3%7D%20%7D%7B3%7D%2C%5C%3A%5C%3Afor%5C%3A%5C%3A%5Cfrac%7B%5Cpi%7D%7B2%7D%5Cle%20x%20%5Cle%20%5Cpi)
Recall that the reciprocal of the cosine ratio is the secant ratio.
This implies that;
![\frac{1}{\cos x}=-\frac{2\sqrt{3} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Ccos%20x%7D%3D-%5Cfrac%7B2%5Csqrt%7B3%7D%20%7D%7B3%7D)
![\Rightarrow \cos x=-\frac{3}{2\sqrt{3} }](https://tex.z-dn.net/?f=%5CRightarrow%20%5Ccos%20x%3D-%5Cfrac%7B3%7D%7B2%5Csqrt%7B3%7D%20%7D)
![\Rightarrow \cos x=-\frac{\sqrt{3}}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20%5Ccos%20x%3D-%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D)
We take the inverse cosine of both sides to obtain;
![x=\cos^{-1}(-\frac{\sqrt{3}}{2})](https://tex.z-dn.net/?f=x%3D%5Ccos%5E%7B-1%7D%28-%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%29)